Ehrlichia canis and Rickettsia conorii Infections in Shelter Dogs: Seropositivity and Implications for Public Health - Paulo Afonso; Ana Patrícia Lopes; Hélder Quintas; Luís Cardoso; Ana Cláudia Coelho (Pathogens, 2024)
A cross-sectional study was conducted to gain insight into the epidemiology of canine ehrlichiosis and rickettsiosis in northern Portugal. Specific IgG antibodies to Ehrlichia canis were analysed using a commercial enzyme-linked immunosorbent assay (ELISA), and antibodies to Rickettsia conorii were analysed using a commercial indirect immunofluorescence antibody test (IFAT). A total of 113 dogs from two different shelters were sampled, and seroprevalence values of 0.9% (95% confidence (CI): 0.2–4.8%) for E. canis and 9.7 (95% CI: 5.5–16.6%) for R. conorii were found. Multiple logistic regression investigated risk factors for seropositivity. The odds ratios (ORs) of R. conorii seropositivity were higher for female dogs (OR = 6.429; 95% CI: 1.201–34.407). Dogs seropositive for co-infection (E. canis + R. conorii) were more frequently observed among females (OR = 7.606; CI 95%: 1.478–39.132) and in Shelter 2 (OR = 18.229; 95% CI: 2.190–151.756). These findings show that shelter dogs in northern Portugal are exposed to E. canis and R. conorii, which can affect both canines and humans. It is imperative to adopt a One Health approach to educate the public about the hazards of canine zoonoses and develop legislation and procedures to control their spread and preserve public health.